2021
DOI: 10.3390/horticulturae8010024
|View full text |Cite
|
Sign up to set email alerts
|

Neglected Potential of Wild Garlic (Allium ursinum L.)—Specialized Metabolites Content and Antioxidant Capacity of Wild Populations in Relation to Location and Plant Phenophase

Abstract: Wild garlic (Allium ursinum L.) is one of the species widely distributed in Europe and Asia and is often nutritionally neglected, characterized by a high content of various phytochemicals with high therapeutic potential and a range of biological activities. The aim of this study was to determine the content of bioactive compounds in the leaves of wild garlic populations collected from different micro-locations, and to determine the differences in the content of phytochemicals in the vegetative and generative p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 14 publications
(19 citation statements)
references
References 44 publications
1
14
0
Order By: Relevance
“…Some studies have also found an increase in the TPC from the budding to flowering stages, which was also observed in this study, wherein the cup plants showed a value of 65%. The reason for the increase in the total phenol content may be the plant’s response to the failed redistribution of phenol in the developing plant parts or part of a defense mechanism against senescence with which the plant responds by producing more phenol [ 36 ].…”
Section: Resultsmentioning
confidence: 99%
“…Some studies have also found an increase in the TPC from the budding to flowering stages, which was also observed in this study, wherein the cup plants showed a value of 65%. The reason for the increase in the total phenol content may be the plant’s response to the failed redistribution of phenol in the developing plant parts or part of a defense mechanism against senescence with which the plant responds by producing more phenol [ 36 ].…”
Section: Resultsmentioning
confidence: 99%
“…It is important to note that AsA biosynthesis in plants is strongly influenced by different factors such as photosynthesis rate, genetic predisposition [ 59 ], stress exposure [ 60 , 61 ], phenophase, etc. AsA is also involved in a number of important metabolic functions in the plant organism, including detoxification of reactive oxygen species (ROS), and is a cofactor for the biosynthesis of some plant hormones (ethylene, gibberellic acid and abscisic acid), which affect the regulation of developmental processes, including senescence and flower formation [ 62 ].…”
Section: Discussionmentioning
confidence: 99%
“…Some studies indicate the significant increase in TPC from the bud to the senescent stage [ 69 ]. The increase of total phenols at the flowering phase may be due to the failure of redistribution of the phenols to the developing parts or by the increased synthesis of phenols toward senescence as part of the defense mechanism [ 62 ], thus mature flowers are possibly a desirable source of these compounds.…”
Section: Discussionmentioning
confidence: 99%
“…are market favorites in the form of processed products. Moreover, numerous wild species are used as food or remedy, mostly as common alliums [20].…”
Section: Usage Of Allium Speciesmentioning
confidence: 99%